Cost-effective reduction of eutrophication in the Gulf of Kalloni (Island of Lesvos, Greece) - ZANOU, B.; KOPKE, A. (Mediterranean Marine Science, 2001)
This study presents a cost-effective analysis by comparing the costs of measures (options) to improve the quality of bathing waters in the Gulf of Kalloni (island of Lesvos, Greece) in order to reduce the anthropogenic eutrophication in the coastal water of the Kalloni Gulf. The Gulf of Kalloni is a semi-enclosed gulf (115 km2) which receives municipal wastewater, agricultural activity drainage, and at times sewage from olive oil plants processing the local olives harvest. The area of study consists of the coastal waters and the river basin of which water run-off drains into the gulf. Four options are comparable in their environmental effectiveness to reduce eurtophication damages which are: municipal wastewater treatment plant, construction of dams, organic farming plus training and olive oil wastewater treatment plant.